Australian Literature and the New Empiricism: A reponse to Paul Eggert, "Australian Classics and the Price of Books" (Journal of the Association for the Study of Australian Literature, 2008)
Australian Literature and the New Empiricism: A reponse to Paul Eggert, "Australian Classics and the Price of Books"